Problems and Improvement Measures in the Cost of Landscaping and Greening - Zhang, Ming (Journal of Theory and Practice of Management Science, 2023)
Engineering cost plays an important role in the construction of landscaping and greening projects, which will directly affect the overall efficiency of the project construction. Landscape greening projects generally fall within the scope of public works, so cost related work needs to be strictly carried out in accordance with relevant procedures. At present, there are still some problems in the construction of landscape greening projects in some regions, and the issues related to project cost are relatively concentrated. Therefore, this article specifically explores the problems and improvement measures that arise in the cost of this project for reference.